2017
DOI: 10.22271/ortho.2017.v3.i4j.91
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of two percutaneous pinning techniques (Cross K wire vs Lateral K wire) for Gartland type III pediatric supracondylar fracture of the humerus

Abstract: Background: Supracondylar fractures of humerus are one of the most common fractures in paediatric age group. Closed reduction and percutaneous K-wire fixation is one of the most commonly used treatment modality in Gartland type 3 fractures. A prospective randomized controlled study was undertaken to compare whether parallel k wires are better in terms of the stability, functional outcome and iatrogenic ulnar nerve as compared to cross k wire (medial and lateral). Material and methods: This is a prospective com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(17 reference statements)
1
3
0
Order By: Relevance
“…Also, higher incidence in males and greater involvement on left side were seen, which is consistent with a study of 57 patients conducted by Naik et al [20] No significant difference in functional outcome was noted between either of the techniques in our study. This finding is comparable to the studies by Naik et al [20] Patil et al [21] Kocher et al [5] and Reynolds et al [22] This shows that the surgeon may choose any of the two techniques to fix the fracture as per his convenience, fracture pattern and surgical skill. Lateral k wire fixation has as good outcome as cross kwire fixation.…”
Section: Discussionsupporting
confidence: 86%
“…Also, higher incidence in males and greater involvement on left side were seen, which is consistent with a study of 57 patients conducted by Naik et al [20] No significant difference in functional outcome was noted between either of the techniques in our study. This finding is comparable to the studies by Naik et al [20] Patil et al [21] Kocher et al [5] and Reynolds et al [22] This shows that the surgeon may choose any of the two techniques to fix the fracture as per his convenience, fracture pattern and surgical skill. Lateral k wire fixation has as good outcome as cross kwire fixation.…”
Section: Discussionsupporting
confidence: 86%
“…The incidence of iatrogenic ulnar nerve injury was compared in 18 RCTs (Table 2 ). Six studies observed no injury in all patients [ 22 , 27 , 30 , 35 37 ]. Among 542 fractures with crossed medial–lateral pinning, there were 22 cases suffering injury of iatrogenic ulnar nerve.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified a total of 327 unique articles after removing duplicates. Finally, 19 RCTs comprising 1297 children with SCHF were included in current meta-analysis [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] (Fig. 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Prospective randomized study Vaidya et al (20) 2009 UNIVERSITY OF SEYCHELLES American Institute of medicine Prospective randomized study Patil et al (21) 2017 International Journal of Orthopaedics Sciences…”
Section: International Journal Of Biomedical Researchmentioning
confidence: 99%